Demographic Characteristics of Pediatric Burn in Shahid Motahhari Hospital from 2007-2011 - Aghakhani, K; Mehrpisheh, Sh; Memarian, A; Taheri, I (International Journal of Medical Toxicology and Forensic Medicine, 2013)
<!–[if gte mso 9]> <![endif]–> Background: Severe burn is one of the major causes of morbidity and mortality in children and adolescents and is third most common cause of death among this age group. The aim of this study was to evaluate demographic characteristics of pediatric burn over a period of 5 years and the relationship between cause mortality in patients with burns. Method: In this cross sectional study, documents of children under 15 years, in Shahid Motahari hospital between 2007 and 2011 was evaluated. Variables such as age, sex, stay duration in hospital, burn cause, severity, accident cause burns and outcome of patients finally entered in SPSS v.16 and were analyzed. Results: In this study, 416 patients (34/8%) were female and 780 (65/2%) were male. Factors for burns in children include boiling water in 674 cases (56/4%), flame in 190 patients (15/9%), burns with flammable materials in 131 cases (11%), burns with a hot meal for 113 people (9/4%) and other hot bodies in 30 patients (2/5) and steam burns in 3 (0/3%). Increasing in burned body surface was significantly associated with mortality (P value= < 0.001). Burn severity in children who died was more than other children (P value= < 0.001). Also burn etiology was significantly different in patients who died and patients were discharged (P Value= 0.003). Conclusion: Based of the results of this study, burn in boys was more than girls and was common inpatients under 2 years of age. Thermal burns were the most common type of burns in children (95/4%) and hot water were also the most important cause in thermal burns in children (56/4%).Burn extent in the majority of children (75%), was less than 30% of the body surface and burns between 50 to 100% occurred in 6/3% of cases. Average stay duration in the hospital was 12/8 days and mortality rate was 7/2%. Area and depth of the burn injury were the most important determinants of mortality.